Samgång av olika arter på svenska djurparker - Sandell, Ann-Sofie (2010)
Zoos currently aim at keeping animals in as natural habitats as possible, since they have gone from displaying exotic animals to working with conservation of endangered species. It is therefore more common that zoos keep groups composed of two or more species in the same enclosure. The aim of this report is to study why and how different species are held at zoos. Species in the wild can interact in different degrees depending on season and resources. When species are held together at zoos the space can be more effectively used, the animals increase their activity and the visitors increase their learning. Mixed species enclosures involve more work and risks of injury. My recommendation for addition to the Swedish directions (L108) is that the animals should have opportunity to retreat when they are held with one or more species, to imitate their natural life as much as possible and decrease the stress it could mean for the animals. To get a view of how common mixed species enclosures are at Swedish zoos, I got in contact with the zoologist on each of the zoos that are members of The Swedish Association of Zoos and Aquaria, SAZA. They answered which species were held together at each zoo and why. Almost all zoos have mixed species enclosures in different extensions and with the aim to give the animals and visitor enrichment at the same time as the animals represent a biotope. More scientific studies are desired, both at mixed species groups in the wild and at zoos.